Developing Conducive Sustainable Outdoor Learning: The Impact of Natural environment on Learning, Social and Emotional Intelligence - Nurakmal, Abdullah@ Goh Tuo Ho; Seyedehzahra, Mirrahimi; Norngainy, Mohd Tawil; Surat, M.; Iliyasu, Usman M. S. (Elsevier Science, Ltd., 2011)
This study propose that outdoor learning engaging with nature environment provide opportunities to improve academic achievement and social emotional intelligence for students; so, the features of landscape have influence to develop acquiring awareness in natural environment, training for sustainability and various green systems, learning in a number of subject areas such as science and Learning by smelling, feeling, tasting. Green schools support personal and social wellbeing at various students' levels. In addition, students can learn how to work together to take responsibilities such as planting by group learning. Access to nature was supposed to develop self- confidence, responsibilities, sense of pride, cooperate, solving problems in classroom, and relationships between students and teachers. This paper describe that a good design outdoor learning engaging with nature is an important role to promote student's abilities such as academic achievement and social behaviours.